Students' Critical Thinking Profile in Solving Problems Proving Trigonometric Identities in View of Gender Differences - Eliyana, Eliyana; Sugita, Gandung; Anggraini, Anggraini; Murdiana, I Nyoman (Universitas Ma'arif Lampung, 2024)
This study aims to describe the critical thinking profile of SMAN 5 Model Palu grade XI students in solving trigonometric identity proof problems regarding gender differences. The subjects in this study were male students or S1 and female students or S2 of grade XI Mipa 4 SMAN 5 Model Palu who have high mathematical abilities. Data were collected through tests and interviews. The results of this study indicate that S1 and S2 in solving trigonometric identity proofs have the correct answers and are accompanied by supporting reasons. However, there are some differences in thinking activities between the two, namely S1 who is a male student with high ability has a shorter answer than the solution of S2 who is a female student with high ability, S1 uses a logical way of thinking compared to S2 who tends to be proficient with his verbal abilities. This shows that S1 and S2 even though they have equal mathematical abilities, there are some differences between the two in solving trigonometric identity proofs whose data are obtained from written assignment answers and interview results.